2021
DOI: 10.1055/s-0041-1730031
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Impact of Infusion Alerts and Alarms on Nursing Workflows: A Retrospective Analysis

Abstract: Background Smart infusion pumps affect workflows as they add alerts and alarms in an information-rich clinical environment where alarm fatigue is already a major concern. An analytic approach is needed to quantify the impact of these alerts and alarms on nursing workflows and patient safety. Objectives To analyze a detailed infusion dataset from a smart infusion pump system and identify contributing factors for infusion programming alerts, operational alarms, and alarm resolution times. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Of the 22 included studies, three identified potential problems associated with the use of IV medication infusion devices [ 26 , 32 , 35 ], and four described the application of interventions or explored the effects of the intervention developed to reduce errors that occur when using IV medication infusion devices [ 24 , 27 , 34 , 39 ]. IV medication infusion devices, such as infusion pumps and smart pumps, are widely used in healthcare environments and allow more rigorous control in the process of administering medications that are continuously infused [ 45 ]. Smart pumps are recognized as useful devices for providing safe and effective nursing care [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 22 included studies, three identified potential problems associated with the use of IV medication infusion devices [ 26 , 32 , 35 ], and four described the application of interventions or explored the effects of the intervention developed to reduce errors that occur when using IV medication infusion devices [ 24 , 27 , 34 , 39 ]. IV medication infusion devices, such as infusion pumps and smart pumps, are widely used in healthcare environments and allow more rigorous control in the process of administering medications that are continuously infused [ 45 ]. Smart pumps are recognized as useful devices for providing safe and effective nursing care [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…We then verified whether the infusion pump settings could be matched with the injection order information. This was not a study of a "smart pump" [7][8][9][10][11] that automatically adjusts the drug speed and dosage; instead, we collected information from the infusion pump and used it for a injection order matching process. Although the linkage of data with smart pumps is innovative, it is not practical to obtain approval from the Japanese regulatory agency, the Pharmaceuticals and Medical Devices Agency.…”
Section: Objectivesmentioning
confidence: 99%
“…The contribution of physiologic monitor and device-based alarms is well described. 48 49 These alerts have long comprised the aural tapestry of many inpatient wards and intensive care units and have been a source of concern for more than a decade, including contribution to alarm fatigue and workflow interruptions. 4 50 However, health care systems have proceeded apace with additional vehicles for delivering interruptive alerts.…”
Section: Beyond the Ehr: A Holistic View Of The Alert Ecosystemmentioning
confidence: 99%